1988
DOI: 10.1139/v88-179
|View full text |Cite
|
Sign up to set email alerts
|

The structure, stereochemistry, and biosynthetic origin of a diterpenoid fungal metabolite, traversianal, established by 1H, 2H, and 13C magnetic resonance

Abstract: The structure of traversianal, a tricyclic diterpenoid fungal metabolite of Cercospora traversiana, has been elucidated through detailed 1H and 13C magnetic resonance studies, including homo- and heteronuclear correlation spectra of the natural product and examination of 13C-labelled material obtained by [1,2-13C2]acetate incorporation experiments. Its stereochemistry was established from a series of nuclear Overhauser effect difference spectra. The tricyclic carbon skeleton of traversianal is that of the fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…this report, the cumulative data indicate that the formation of (2) is facilitated by an energetically rather unfavorable tandem cis-hydride transfer. This mechanistic feature has also been reported in the biocatalysis of fusiccocin (Stoessl et al, 1988;Banerji et al, 1978), and it is a likely option in the formation of dolabellane and cyclooctat-9-en-7-ol. Therefore, a consecutive cis-hydride transfer may be a particular feature of the biosynthesis of fusicoccane-type macrocycles.…”
Section: Importance Of Cotb2 W288g For Carbocation Migrationsupporting
confidence: 67%
“…this report, the cumulative data indicate that the formation of (2) is facilitated by an energetically rather unfavorable tandem cis-hydride transfer. This mechanistic feature has also been reported in the biocatalysis of fusiccocin (Stoessl et al, 1988;Banerji et al, 1978), and it is a likely option in the formation of dolabellane and cyclooctat-9-en-7-ol. Therefore, a consecutive cis-hydride transfer may be a particular feature of the biosynthesis of fusicoccane-type macrocycles.…”
Section: Importance Of Cotb2 W288g For Carbocation Migrationsupporting
confidence: 67%
“…The results indicated that the active compound was traversianal, a diterpenoid aldehyde with a molecular weight of 316.4. Traversianal has been isolated from Cercospora traversiana, a pathogen of fenugreek, one of the oldest medicinal plants originating from India and North Africa, and has a 5-8-5 tricyclic carbon skeleton (Stoessl et al 1988). Stoessl et al (1989) examined the biological properties of traversianal and reported that it is highly toxic at low concentrations to brine shrimp and snails and lyses human red blood cells at 5 × 10 − 7 M. Additionally, the study reported that traversianal has no harmful effects on oral crop intubation (100 mg/kg) or any other level tested on chicks and is not toxic to various bacteria and fungi in standard growth and germination inhibition tests.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids with dicyclopenta[a,d]cyclooctane (5-8-5) carbon skeleton are fairly broadly distributed in Nature. Sesterterpenoid, ophiobolin A ( 1 ), and its congeners were first isolated from a plant pathogenic fungus, Ophiobolus miyabeanus , and reported in 1965. Somewhat later a diterpenoid of the same tricyclic core, fusicoccin A ( 2 ), was obtained from a culture of fungus, Fusicoccum amygdali , responsible for a wilting disease of peach and almond trees in Southern Europe. , Since then several other 5-8-5 di- and sester-terpenoids were isolated from various fungi, insect wax, , brown alga, liverworts, and plants. Compounds 1 and 2 are characterized by the presence of multiple oxygen-containing functional groups. However, hydrocarbon terpenes such as cycloaraneosene ( 3 ) or those bearing a scarce oxygen functions, as epoxydictymene ( 4 ) were also obtained from natural sources (see Scheme ).
1 Structures of Representative Ophiobolanes and Fusicoccanes
…”
Section: Introductionmentioning
confidence: 99%